Effects of Positive, Negative, and Punishment Reinforcement on Motivation at College’s Students in Indonesia - S. Marinda, Vina; R. Suhardi, Agatha (International Journal of Psychosocial Rehabilitation, 2020)
Motivation is a process carried out by someone to achieve their goals. Motivation in supporting the achievement of goals is caused by reinforcement (positive reinforcement, negative reinforcement, and/or punishment reinforcement). This study used a case study in the Faculty of Business and Management at one of the universities in Indonesia. The purpose of this study is to address how positive reinforcement, negative reinforcement, punishment reinforcement, and motivation affect college’s students in Indonesia and also to show how positive reinforcement, negative reinforcement, and/or punishment reinforcement affect motivation at college’s students in Indonesia. This type of study is explanatory research to know the causal relationship between positive reinforcement, negative reinforcement, and punishment reinforcement on motivation at college’s students in Indonesia. The research method used is multiple linear regression analysis. Findings of this study showed that positive reinforcement has a positive and significant effect on college’s students in Indonesia, but negative reinforcement and punishment reinforcement have no significant effect.